A chitosan-based polyaniline-Au nanocomposite biosensor for determination of cholesterol - Srivastava M.; Srivastava S.K.; Nirala N.R.; Prakash R. (My University, 2025)
A polyaniline-gold (PAni-Au) nanocomposite is chemically synthesized and impregnated in a chitosan matrix for immobilization of cholesterol oxidase on an indium tin oxide-coated glass plate for development of cholesterol biosensors. The PAni-Au nanocomposite is characterized for structural and thermal properties. Further the PAni-Au nanocomposite is used for cholesterol oxidase immobilization and linkage is examined by FTIR. The nanocomposite is used to form a modified bioelectrode by immobilizing cholesterol oxidase in the chitosan matrix and examined under an optical microscope for uniformity and morphological studies. A modified bioelectrode (ChOx/PAni-Au-CH/ITO) is used to detect cholesterol by using a voltammetric technique with a redox mediator. The sensor exhibits linearity in a wide range of 50-500 mg dL-1 with a detection limit of 37.89 mg dL-1, a sensitivity of 0.86 μA mg dL-1 and a shelf life of more than 3 weeks when stored at 4 °C. Voltammetric studies have also been carried out with common possible interferents. Responses are recorded to get enzyme-substrate kinetics for the biosensor and found as Km = 10.84 mg dL-1. The low value of Km indicates that the prepared nanocomposite facilitates the enzymatic reaction and enzymatic activity. Excellent immobilization and enzyme-substrate reactions show a distinct advantage of this matrix over other matrixes used for cholesterol biosensors. The novelty of the prepared electrode lies in its reusability, higher sensitivity, better shelf life, and accuracy. © 2014 The Royal Society of Chemistry.